2011
DOI: 10.1103/physrevc.83.021903
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triangular flow on di-hadron azimuthal correlations in relativistic heavy ion collisions

Abstract: Using the AMPT model for relativistic heavy ion collisions, we have studied the di-hadron azimuthal angular correlations triggered by emitted jets in Au+Au collisions at center of mass energy √ sNN = 200 GeV and impact parameter b = 8 fm. A double-peak structure for the associated particles at the away side of trigger particles is obtained after subtracting background correlations due to the elliptic flow. Both the near-side peak and the away-side double peaks in the azimuthal angular correlations are, however… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…Measurements of dihadron correlations at RHIC have frequently attempted to subtract or factorize the elliptic flow contribution based on direct v 2 measurements, in order to reveal other features of particle correlations that may provide insight into the interactions between the jets and the medium. However, recent theoretical developments indicate that the interplay between initial-state fluctuations and the subsequent hydrodynamic expansion gives rise to additional Fourier components in the azimuthal particle correlations [25,26,[38][39][40][41][42]. These components need to be treated on equal footing with the elliptic flow component.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of dihadron correlations at RHIC have frequently attempted to subtract or factorize the elliptic flow contribution based on direct v 2 measurements, in order to reveal other features of particle correlations that may provide insight into the interactions between the jets and the medium. However, recent theoretical developments indicate that the interplay between initial-state fluctuations and the subsequent hydrodynamic expansion gives rise to additional Fourier components in the azimuthal particle correlations [25,26,[38][39][40][41][42]. These components need to be treated on equal footing with the elliptic flow component.…”
Section: Resultsmentioning
confidence: 99%
“…Motivated by recent theoretical developments in understanding the long-range ridge effect in the context of higher-order hydrodynamic flow induced by initial geometric fluctuations, such as the "triangular flow" effect [26,[38][39][40][41][42], an alternative way of quantifying the observed long-range correlations is investigated in this paper. The 1-D ∆φ-projected distribution for 2 < |∆η| < 4 is decomposed in a Fourier series as 2) JHEP07 (2011) where N assoc represents the total number of hadron pairs per trigger particle for a given |∆η| range and (p trig T , p assoc T ) bin.…”
Section: Fourier Decomposition Of ∆φ Distributionsmentioning
confidence: 99%
“…In fact, because of the nonsmooth profile, coming from the event-byevent fluctuations of participant nucleons, it shows a triangular initial geometry shape can be transferred into momentum space by hydrodynamical evolution. In recent studies, it has been demonstrated that triangular flow significantly contributes on the near-side ridge and away-side double bumps in two-particle azimuthal correlations [16,17]. As a probe, triangular flow is believed to provide more information about the formed hot and dense matter.…”
Section: Introductionmentioning
confidence: 98%
“…Concentrating on large | η|, previous measurements at RHIC established some of the properties of the so-called "ridge" [4,6,9], an enhancement of pairs with | φ| ≈ 0. While a variety of theoretical models have been proposed to interpret the ridge phenomena as a consequence of jet-medium interactions [14][15][16][17][18][19], recent theoretical developments indicate that, because of event-byevent fluctuations in the initial shape of the interacting region, sizeable higher-order hydrodynamic flow terms could also be induced, e.g., triangular flow [20][21][22][23][24][25][26][27][28]. The triangular flow effect will contribute to the dihadron correlations in the form of a cos(3 φ) component, which also gives a maximum near-side correlation at φ ≈ 0, similarly to the elliptic flow contribution.…”
Section: Introductionmentioning
confidence: 99%